Schumann Resonances and the Human Body: Questions About Interactions, Problems and Prospects - Ganna Nevoit; Mantas Landauskas; Rollin McCarty; Inga Arune Bumblyte; Maksim Potyazhenko; Giedre Taletaviciene; Gediminas Jarusevicius; Alfonsas Vainoras (Applied Sciences)
(1) Background: The interaction between the human body and the Earth’s magnetic field at Schumann resonances (SRs) is one of the important fundamental questions of science that continues to be studied. The aim of this study was to create a working theoretical foundation for the interaction of the human body with SRs. (2) Methods: Extensive research was carried out in the literature with the aim of comprehensively presenting data on SRs and creating a working concept of their interaction with the human body. (3) Results: General data on SRs, a theoretical basis for justifying their interaction with the human body, possible mechanisms of influence and research results on the functioning of human internal organs were presented. (4) An interaction of the human body with SRs exists and has been scientifically proven. This interaction has been studied most significantly between SRs and the human nervous system. SRs affect functional indicators of the cardiovascular system: heart rate and blood pressure. Studying the influence of SRs on the course and pathogenesis of non-communicable diseases is a promising direction. Low-frequency SRs decrease the risk of developing acute myocardial infarction, and there is a tendency for them to promote cases of chronic kidney disease. SRs are an important external natural factor influencing the human body.